2018
DOI: 10.1029/2018sw001983
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to NASA Living With a Star Institute Special Section on Low Earth Orbit Satellite Drag: Science and Operational Impact

Abstract: This paper provides a brief description of the NASA Living With a Star (LWS) Institute special section on low Earth orbit (LEO) satellite drag: Science and operational impact. The goals of the LWS institute are to (a) review the current status of atmospheric drag research and operational concerns for LEO satellites, (b) identify and understand the major issues in atmospheric drag estimation, and (c) provide recommendations for future improvement in our ability to provide nowcasts of satellite drag. This specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Among these processes, intense, CME‐driven geomagnetic storms lead to the largest neutral density increase. It is also identified that errors in the thermosphere density specification are the dominant source in uncertainty of LEO satellite conjunction (Zhang et al., 2018 and the references therein). Accurate measurement of neutral density profiles and their variations becomes critical for LEO position nowcast and forecast capability development as the LEO space becomes more crowded and the demands for precise position information grow.…”
Section: Introductionmentioning
confidence: 99%
“…Among these processes, intense, CME‐driven geomagnetic storms lead to the largest neutral density increase. It is also identified that errors in the thermosphere density specification are the dominant source in uncertainty of LEO satellite conjunction (Zhang et al., 2018 and the references therein). Accurate measurement of neutral density profiles and their variations becomes critical for LEO position nowcast and forecast capability development as the LEO space becomes more crowded and the demands for precise position information grow.…”
Section: Introductionmentioning
confidence: 99%
“…These features serve to illustrate the wide range of local processes that influence the neutral density (Emmert, 2015;Liu et al, 2017). These large-scale structures in the ionosphere and thermosphere have significant impacts on satellite drag (e.g., Zhang et al, 2018) and on radio scintillation. Many have been studied in detail, such as field-aligned ion drag (Maruyama et al, 2003;Miyoshi et al, 2011), chemical heating by charge exchange (Fuller-Rowell et al, 1997), and heat transport due to the background wind (Hedin & Mayr, 1973) and tidal propagation (Miyoshi et al, 2011).…”
Section: Neutral Density Variations By Large-scale Processesmentioning
confidence: 99%
“…Errors in the estimation of density cause orbit prediction error, which impact satellite operations, including accurate catalog maintenance, collision avoidance for manned and unmanned space flight, and re‐entry prediction (Qian & Solomon, ). These effects were also highlighted in a recent National Aeronautics and Space Administration Living With a Star Institute special section on low Earth orbit (LEO) satellite drag: Science and operational impact, which reported that errors in the thermosphere density specification are the dominant source in uncertainty of LEO drag estimation and satellite conjunction (Zhang et al, ).…”
Section: Introductionmentioning
confidence: 95%